Avascular necrosis of stapes crura in one case of operated otosclerosis - Erdoglija, Milan; Sotirovic, Jelena; Jacimovic, Violeta; Vukomanovic, Biserka (Acta Medica, 2012)
Unilateral otosclerosis combined with avascular necrosis of stapes crura is a rare entity. It should be considered in a case of high grade otosclerosis. Symptoms are the same as in patients who suffer from common otosclerosis. Patients complain on progressive hearing loss and tinnitus. The diagnosis is made clinically by conventional audiologic evaluation and radiologically by x-ray mastoid Schuller's view and CT scan. HRCT scan makes visible all parts of ossicular chain and gives surgeon some information about ossicular chain damage. Surgery with stapedotomy and stapes prosthesis implantation in a case of otosclerosis with avascular necrosis of stapes crura can be success therapy to improve patient's hearing
Keywords: mužské pohlaví; nekróza; Humans; otoskleróza; stapes; chirurgie třmínku; lidé; dospělí; Stapes Surgery; Necrosis; Stapes; Male; Adult; Otosclerosis